2010
DOI: 10.1093/neuonc/noq050
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of human glioblastomas are associated with both tumor cytogenetics and histopathology

Abstract: Despite the increasing knowledge about the genetic alterations and molecular pathways involved in gliomas, few studies have investigated the association between the gene expression profiles (GEP) and both cytogenetics and histopathology of gliomas. Here, we analyzed the GEP (U133Plus2.0 chip) of 40 gliomas (35 astrocytic tumors, 3 oligodendrogliomas, and 2 mixed tumors) and their association with tumor cytogenetics and histopathology. Unsupervised and supervised analyses showed significantly different GEP in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 44 publications
(26 reference statements)
1
50
0
Order By: Relevance
“…Consistent with previously published studies, the gene signature of Verhaak et al (6) stratified TCGA GBM samples (n = 385) into four subtypes (mesenchymal, proneural, neural, and classical), whereas the gene signature of Phillips et al (5) classified these tumors into three subtypes (mesenchymal, proneural, and proliferative). We compared mesenchymal and proneural subtypes because these are the only common subgroups in the classification methods of Verhaak et al and Phillips et al Moreover, genomic analyses by other research groups have revealed the existence of two to four major hierarchical groupings of GBM (16,17). Huse et al (18) reviewed the different classification methods and suggest that the proneural and mesenchymal distinction is a common theme that emerges across different clustering approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previously published studies, the gene signature of Verhaak et al (6) stratified TCGA GBM samples (n = 385) into four subtypes (mesenchymal, proneural, neural, and classical), whereas the gene signature of Phillips et al (5) classified these tumors into three subtypes (mesenchymal, proneural, and proliferative). We compared mesenchymal and proneural subtypes because these are the only common subgroups in the classification methods of Verhaak et al and Phillips et al Moreover, genomic analyses by other research groups have revealed the existence of two to four major hierarchical groupings of GBM (16,17). Huse et al (18) reviewed the different classification methods and suggest that the proneural and mesenchymal distinction is a common theme that emerges across different clustering approaches.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed information of the identified regions by the six methods is given in Table S2. Based on a large collection of previous studies on glioblastoma patients [3], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], we summarize the numbers of glioblastoma related regions resulted by the methods for a further comparison. This is shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…RFX 4 (regulatory factor X 4), a transcription factor known to influence HLA Class II expression is overexpressed in gliomas compared to normal brain tissues [43]. In another study, STXBP6 (syntaxin binding protein 6-amisyn) that is known to be involved in vesicle-mediated intracellular transport was found to be differentially expressed in high versus low grade gliomas [45]. Taken together the data not only validates the ANN approach utilized in the current study but also suggests a complex interaction between DNA repair, transcription and other essential cellular processes in glioma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%